Buchrezension zu: Natürliche und künstliche Intelligenz - Heiko Neumann (BIOspektrum, 2025)

Canonical circuit computations for computer vision - Daniel Schmid; Christian Jarvers; Heiko Neumann (Biological Cybernetics, 2023)
Advanced computer vision mechanisms have been inspired by neuroscientific findings. However, with the focus on improving benchmark achievements, technical solutions have been shaped by application and engineering constraints. This includes the training of neural networks which led to the development of feature detectors optimally suited to the application domain. However, the limitations of such approaches motivate the need to identify computational principles, or motifs, in biological vision that can enable further foundational advances in machine vision. We propose to utilize structural and functional principles of neural systems that have been largely overlooked. They potentially provide new inspirations for computer vision mechanisms and models. Recurrent feedforward, lateral, and feedback interactions characterize general principles underlying processing in mammals. We derive a formal specification of core computational motifs that utilize these principles. These are combined to define model mechanisms for visual shape and motion processing. We demonstrate how such a framework can be adopted to run on neuromorphic brain-inspired hardware platforms and can be extended to automatically adapt to environment statistics. We argue that the identified principles and their formalization inspires sophisticated computational mechanisms with improved explanatory scope. These and other elaborated, biologically inspired models can be employed to design computer vision solutions for different tasks and they can be used to advance neural network architectures of learning.

Impact of diesel exhaust exposure on urinary 1-hydroxypyrene in underground salt and potash workers - Swaantje Casjens; Savo Neumann; Katrin Rühle; Lisa Gamrad-Streubel; Lisa-Marie Haase; Katharina K. Rudolph; Thomas Birk; Jörg Giesen; Volker Neumann; Dirk Pallapies; Jürgen Bünger; Heiko U. Käfferlein; et al. (International Journal of Hygiene and Environmental Health, 2023)

Interaction of ON and OFF pathways for visual contrast measurement - Heiko Neumann; Luiz Pessoa; Thorsten Hansen (Biological Cybernetics, 2008)

Globally consistent depth sorting of overlapping 2D surfaces in a model using local recurrent interactions - Axel Thielscher; Heiko Neumann (Biological Cybernetics, 2008)

Visual filling-in for computing perceptual surface properties - Heiko Neumann; Luiz Pessoa; Thorsten Hansen (Biological Cybernetics, 2001)

Combined space-variant maps for optical-flow-based navigation - Gregory Baratoff; Christian Toepfer; Heiko Neumann (Biological Cybernetics, 2000)

Recurrent V1-V2 interaction in early visual boundary processing - Heiko Neumann; Wolfgang Sepp (Biological Cybernetics, 1999)

Interaction of ON and OFF pathways for visual contrast measurement - Heiko Neumann; Luiz Pessoa; Thorsten Hanse (Biological Cybernetics, 1999)